Perceived Concerns and Psychological Distress of Healthcare Workers Facing Three Early Stages of COVID-19 Pandemic - Richaud, María Cristina; Eidman, Leandro; Vargas Rubilar, Jael; Lemos, Viviana; Mesurado, Belén; Klos, María Carolina; Rodriguez de Behrends, Marisa; Muzio, Rubén N. (Frontiers in Psychology, 2022)
Background: The present study analyzed the difference in psychological distress of the healthcare workers in three different periods of the COVID-19 pandemic in Argentina, from the third week of the mandatory quarantine through the two following weeks. Method: It was based on the analysis of the responses of 1458 members of the health personnel to a questionnaire on healthcare workers concerns regarding the care of patients with coronavirus, indicators of depression, anxiety, intolerance of uncertainty, and coping. Results: The psychological indicators considered presented differences between the evaluated periods. Perceived concerns about the possibility of infecting loved ones, as well as infecting themselves, were greatest in the periods after the onset of the pandemic. In addition, the perception of how the work environment worsened and how lack of sleep interfered with their work, was also higher in periods 2 and 3. The same results were found in the indicators of depression, anxiety and intolerance of uncertainty. Finally, the indicators of high tension and at the same time the lack of emotional control, which was greater in the last periods evaluated, were also expressed in the coping strategies (showing emotional lability, only contained by hypercontrol). Conclusions: The differences found in the psychological indicators between the evaluated periods support the need for early psychological care of health personnel, which should be a priority of public health, a fundamental fact to increase its immediate effectiveness in the care of infected patients.